Humanistic Counseling and Student Learning Motivation - Kustinah, Etty; Kambali, Kambali; Lama’atushabakh, Marwah (Qualitative and Quantitative Research Center, 2022)
In the learning process of course, some things hinder the learning process, especially learning motivation. This study aims to raise issues and efforts to increase student motivation at MTSN (State Islamic Junior High School) 11 Cirebon with the humanistic counseling method. This study uses a qualitative method with a descriptive approach. The study results show that the humanistic counseling method has been applied at MTSN 11 Cirebon. Teachers cannot only rely on one method but need to integrate humanistic, behavioristic, and psychoanalytic. Some of the problems of student motivation at MTSN 11 Cirebon are the lack of student activity in the classroom, students still being reluctant to the teacher, a crisis of self-confidence, not collecting assignments, etc. As for some of the efforts and basic techniques of teachers using humanistic counseling, the first is to combine humanistic values ​​in the counseling system, such as self-awareness, freedom of opinion, responsibility, search for meaning in the learning process, and respect for time. Second, the teacher tries to help students to have a correct understanding of learning motivation. The teachers are very important in helping students to study well so that learning outcomes are maximized.